Critical Fujita Exponents for Nonlocal Reaction Diffusion Systems (Journal of Partial Differential Equations, 1999)
In this paper, we prove the existence of critical Fujita exponents for a class of nonlocal reaction diffusion systems. And it is proved that the critical Fujita exponents belong to the blow up case.